Forming chondrules in impact splashes: II. volatile retention - Dullemond, Cornelis; Harsono, Daniel; Stammler, Sebastian Markus (The astrophysical journal, 2016)
Solving the mystery of the origin of chondrules is one of the most elusive goals in the field of meteoritics. Recently, the idea of planet(esimal) collisions releasing splashes of lava droplets, long considered out of favor, has been reconsidered as a possible origin of chondrules by several papers. One of the main problems with this idea is the lack of quantitative and simple models that can be used to test this scenario by directly comparing to the many known observables of chondrules. In Paper I of this series, we presented a simple thermal evolution model of a spherically symmetric expanding cloud of molten lava droplets that is assumed to emerge from a collision between two planetesimals. The production of lava could be either because the two planetesimals were already in a largely molten (or almost molten) state due to heating by 26 Al, or due to impact jetting at higher impact velocities. In the present paper, number II of this series, we use this model to calculate whether or not volatile elements such as Na and K will remain abundant in these droplets or whether they will get depleted due to evaporation. The high density of the droplet cloud (e.g., small distance between adjacent droplets) causes the vapor to quickly reach saturation pressure and thus shuts down further evaporation. We show to what extent, and under which conditions, this keeps the abundances of these elements high, as is seen in chondrules. We find that for most parameters of our model (cloud mass, expansion velocity, initial temperature) the volatile elements Mg, Si, and Fe remain entirely in the chondrules. The Na and K abundances inside the droplets will initially stay mostly at their initial values due to the saturation of the vapor pressure, but at some point start to drop due to the cloud expansion. However, as soon as the temperature starts to decrease, most or all of the vapor recondenses again. At the end, the Na and K elements retain most of their initial abundances, albeit occasionally somewhat reduced, depending on the parameters of the expanding cloud model. These findings appear to be qualitatively consistent with the analysis of Semarkona Type II chondrules by Hewins et al. who found evidence for sodium evaporation followed by recondensation.